Afrika im Ludwig Forum : Skizzen eines Projektes. - Becker, Wolfgang; Beier, Ulli; Bender, Wolfgang; Duala-M'bedy, L.J. Bonny; Kimmerle, Heinz; Luchesi, Elisabeth; Mikangou, Franklin N'Kangou; Taskov-Köhler, Nadja; Uelsberg, Gabriele; van Beek, Wouter E.; Iwalewa-Haus, Bayreuth; Afrika im Ludwig Forum : Skizzen eines Projektes, Ludwig Forum für Internationale Kunst, Aachen, 19.8.1993 - 23.1.1994 (Aachen : Ludwig Forum für Internationale Kunst Aachen, 1993)
Ahearn, John ; Ayon, Belkis ; Baselitz, Georg ; Basquiat, Jean-Michel ; Warhol, Andy ; Bugaev, Sergei ; Anufriev, Sergei ; Buthe, Michael ; Dahn, Walter ; Daze ; Delprat, Hélène ; Lugossy, Lászlo fe ; Fischl, Eric ; Gomez, Louis ; Graves, Nancy ; Hanson, Duane ; Haring, Keith ; Hitzler, Franz ; Quinones, Lee ; Mata, Attila ; Mazzag, István ; Olsvang, Anton ; Penck, A.R. ; Ramos, Mel ; Castelli, Salomé ; Samu, Géza ; Scharf, Kenny ; Smyth, Ned ; Walla, August ; Nolde, Emil ; Man Ray ; Arman ; Bruly-Bouabré, Frédéric ; Altenbourg, Gerhard ; Camp, Sokari Douglas ; Ntiro, Sam J. ; Rehberger, Tobias
Duits
boek
Keywords: Afrika